2011
DOI: 10.1007/s10824-011-9144-4
|View full text |Cite
|
Sign up to set email alerts
|

How cultural organizations’ size and funding influence innovation and performance: the case of museums

Abstract: Our work pursues a twin aim. Firstly, we explore the influence of organizational size on innovations in museums as well as its impact on museums' economic, market and social performance. Secondly, we analyse how the (publicprivate) funding of such organizations impacts innovation and performance. The empirical work is based on information from a survey of 491 museums (British, French, Italian and Spanish). We find that museum size does prove relevant in the commitment to engage in innovation but that public fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 41 publications
(64 reference statements)
1
67
0
1
Order By: Relevance
“…Our results are also consistent with the findings of Pencarelli et al [14], who emphasized that Italian museums are motivated to invest in social sustainability policies, because in this way, they can ensure their future. At the same time, socially responsible behavior allows museums to receive a higher level of public funding, which has a positive influence on their performance in terms of cultural heritage preservation [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are also consistent with the findings of Pencarelli et al [14], who emphasized that Italian museums are motivated to invest in social sustainability policies, because in this way, they can ensure their future. At the same time, socially responsible behavior allows museums to receive a higher level of public funding, which has a positive influence on their performance in terms of cultural heritage preservation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Those who failed to implement such strategies were forced to sell works from their collections, or even merge with other museums to survive [17]. Given the limited and often insufficient financial resources of museums and the fact that they must incur certain costs in order to perform conservation and restoration activities [45], we assume that an increase in effectiveness and performance can positively influence cultural sustainability.…”
Section: Defining the Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Camarero et al . 's research work (, p. 254), there are three types of performance measurements in art organizations. There are existing economic measurements for their profitability and their costs, market measurements related to visitors' perspective and brand recognition, and social performance dimensions related to the degree of fulfilling their mission and vision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, this works like a spiral as larger budgets allow these organizations to attract more effective board members. Camarero et al (2011) suggests that technological, organizational, or in content creative innovations affect positively the economic and social performances of a museum. In fact, a more recent study based on 386 British, French, and Spanish museums found that product, technological, and organizational innovations influence museums positively and help them to achieve their social targets (Garrido & Camarero, 2009).…”
Section: Innovations That Influence Art Organizations' Performancementioning
confidence: 99%